Short enantioselective synthesis of (-)-chloramphenicol and (+)-thiamphenicol using tethered aminohydroxylation - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugarn (Tetrahedron, 2006)
An efficient enantioselective synthesis of (-)-chloramphenicol (1) and (+)-thiamphenicol (2) is described. These antibiotics have been synthesized from commercially available 4-nitrobenzaldehyde and 4-(methylthio)benzaldehyde, respectively, using tethered amino-hydroxylation and Sharpless asymmetric epoxidation as the chirality inducing steps. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: asymmetric epoxidation; Asymmetric synthesis; Kinetic resolution; Tethered aminohydroxylation

Efficient organocatalytic route to the atorvastatin side-chain - George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An organocatalytic route to the synthesis of the atorvastatin side-chain, a building block present in the statin family, is described using L-proline-catalyzed alpha-aminooxylation of an aldehyde. The method also employs an iodine-induced intramolecular electrophilic cyclization of a carbonate to produce the iodocarbonate in a highly diastereoselective manner. (C) 2007 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone via Rh-catalyzed diastereoselective oxidative C-H aminations - Narina, Srinivasarao V.; Kumar, Talluri Siva; George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An efficient enantioselective synthesis of (-)-cytoxazone (1) and (+)-epi-eytoxazone (2) using proline-catalyzed asymmetric alpha-amino-oxylation of aldehydes followed by Rh-catalyzed diastereoselective oxidative C-H amination as the key steps is described. syn or anti 1,2-aminoalcohols were obtained by Rh-catalyzed intramolecular amidation of the C-H bonds of carbamates or sulfamate esters with good to excellent diastereoselectivity. (c) 2006 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of tarchonanthuslactone using proline-catalyzed asymmetric alpha-aminooxylation - George, Shyla; Sudalai, Arurnugam (Tetrahedron-Asymmetry, 2007)
A practical enantio selective synthesis of tarchonanthuslactone 1, an important natural product with a polyol unit, is described. The sequence of synthetic reactions involves proline-catalyzed alpha-aminooxylation and iodine-induced electrophilic cyclization as the chiral inducing steps. (c) 2007 Elsevier Ltd. All rights reserved.

NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides with high diastereoselectivity: a short route to (-)-cytoxazone and droxidopa - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letter, 2007)
The NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides was achieved using lithium bromide as the bromine source under acidic conditions at rt to afford the corresponding chiral alpha-bromo-beta-hydroxy carboxamides. Excellent yields (77-90%) and diastereoselectivities (up to 10:1) along with exclusive control over regio- as well as anti-selectivity are the main features with a good scope of substrates. The method has successfully been applied in the enantioselective syntheses of two biologically important molecules, viz (-)-cytoxazone and L-threo-DOPS (droxidopa). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric bromohydroxylation; Carboxamide; cytoxazone; droxidopa; NaIO4

Short enantioselective synthesis of (-)-bestatin via L-proline-catalyzed alpha-amination of an aldehyde - George, Shyla; Suryavanshi, Gurunath S.; Sudalai, Arumugam (Tetrahedron Letters, 2008)
A short and high yielding enantioselective synthesis of (-)-bestatin, a naturally occurring aminopeptidase inhibitor, is described Via L-proline-catalyzed asymmetric alpha-amination of 3-phenylpropionaldehyde as the key reaction. The methodology also involves a Pd-catalyzed intramolecular cyclization of an allylic acetate giving a trans-oxazoline in a highly diastereoselective manner (dr > 14:1). (C) 2008 Elsevier Ltd. All rights reserved.

Short enantioselective synthesis of guggultetrol, a naturally occurring lipid - George, Shyla; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2010)
An enantioselective synthesis of the naturally occurring lipid, guggultetrol, is described with an overall yield of 24% starting from commercially available 1-pentadecanol in ten linear steps. The key chiral-inducing steps include a Sharpless asymmetric epoxidation of allylic alcohol and a dihydroxylation of an alpha,beta-unsaturated ester. (C) 2010 Elsevier Ltd. All rights reserved.